Cytotoxic activity of the Red Sea anemone entacmaea quadricolor on liver cancer cells - El Salakawy, Noha Moataz (AUC Knowledge Fountain, 2018)
Entacmaea quadricolor (Phylum Cnidaria, class Anthozoa) is a marine anemone found in Coral Reefs in the Red Sea. Its venom is reported to be a potential anticancer agent when tested on several cancer cell lines; such as skin cancer, and lung cancer cell lines. Yet, none of the earlier studies have characterized the extracted venom, nor tested its activity on hepatocellular carcinoma (HCC). The purpose of this study was to determine for the first time the potential cytotoxic activity of the Red Sea anemone E. quadricolor on HCC cell line. In addition to the effects of bleaching, seasonality and light exposure during storage on the venom were studied. Moreover, it was aimed to determine whether the cytotoxic activity was apoptotic or necrotic. In this study, the venom of the anemone E. quadricolor was extracted and stored under three different conditions; winter vs. summer, light vs. dark and bleached vs. unbleached. The cytotoxic activity of each venom was tested on SNU-449 HCC cells using the MTT assay. SDS-PAGE was used to differentiate between venoms based on protein composition. Moreover, Annexin-V/PI assay was used to determine the type of cytotoxic activity. The results revealed that E. quadricolor had potent cytotoxic activity against SNU-449 cells that was mediated by a necrotic pathway. The maximum activity was found during summer at the half-inhibitory concentration (IC50) of 20 Âµg/ ml. However, this cytotoxic activity was neutralized when the venom had been exposed to light when stored. Furthermore, cytotoxic activity was significantly decreased upon Bleaching of the anemone. A protein of 28 kDa was found in the composition of the venoms of bleached and unbleached organisms possibly identifying the cytotoxic active protein. The present results underline the findings of previous studies showing the cytotoxic activity of the sea anemone venom on cancer cell lines extending this to HCC. Furthermore, the findings are unique in showing that a bleached organism still produces toxic proteins and the venom loses its toxicity when exposed to light.